Sun, Sea and Shrines: Application of analytic hierarchy process (AHP) to assess the attractiveness of six cultural heritage sites in Phuket (Thailand) - Božić, Sanja; Vujičić, Miroslav; Kennell, James; Besermenji, Snežana; Solarević, Milica (Geographica Pannonica, 2018)
In order to make recommendations for the diversification of tourism products on the Thai island ofPhuket, this paper applies the analytic hierarchy process (AHP) method to rank the attractiveness of sixcultural heritage sites in the island of Phuket to make recommendations for sites that could be incorporatedin to cultural tourism development in the region. In addition, it applies a quantitative-qualitativeevaluation structure with weighted criteria, based on local expert opinion. The research identified whichof the many potential cultural tourism sites would be the most attractive to tourists and shows the utilityof the AHP method, combined with quantitative-qualitative evaluation, for decision making in tourism destination development contexts.
Keywords: Analytic hierarchy process (AHP); cultural tourism; cultural heritage; diversification; Thailand